Deferred Imitation and Social Communication in Speaking and Nonspeaking Children With Autism. (December 2013) - Strid, Karin; Heimann, Mikael; Gillberg, Christopher; Smith, Lars; Tjus, Tomas
Deferred imitation and early social communication skills were compared among speaking and nonspeaking children with autism and children developing typically. Overall, the children with autism showed a lower frequency on measures of deferred imitation and social communication compared with typically developing children. Deferred imitation was observed at a significantly lower level among the speaking and nonspeaking groups of children with autism. However, when comparing the speaking autism group with the typical group, many differences in observed social communication disappeared. These results underscore the importance of considering children's verbal ability in autism research and clinical practice, and indicate that there are specific difficulties in deferred imitation in autism but that the social communication deficits that are observed are greatly influenced by low level of verbal ability.